Inflation, Money Demand, and Purchasing Power Parity in South Africa - Jonsson, Gunnar (IMF Working Papers; Working Paper ;, 1999)
This empirical study for South Africa indicates that there exists a stable money demand type of relationship among domestic prices, broad money, real income, and interest rates, as well as a long-run relationship among domestic prices, foreign prices, and the nominal exchange rate. In the short run, shocks to the nominal exchange rate affect domestic prices but have virtually no impact on real output, while shocks to broad money have a temporary impact on real output before becoming inflationary. Both types of shocks seem to trigger a monetary policy response, since the short-term interest rate adjusts quickly.